Immunomodulatory Role and Therapeutic Potential of Non-Coding RNAs Mediated by Dendritic Cells in Autoimmune and Immune Tolerance-Related Diseases - Liu, Yifeng; Wang, Xiaoze; Yang, Fan; Zheng, Yanyi; Ye, Tinghong; Yang, Li (Frontiers in Immunology, 2021)
Dendritic cells (DCs) are professional antigen-presenting cells that act as a bridge between innate immunity and adaptive immunity. After activation, DCs differentiate into subtypes with different functions, at which point they upregulate co-stimulatory molecules and produce various cytokines and chemokines. Activated DCs also process antigens for presentation to T cells and regulate the differentiation and function of T cells to modulate the immune state of the body. Non-coding RNAs, RNA transcripts that are unable to encode proteins, not only participate in the pathological mechanisms of autoimmune-related diseases but also regulate the function of immune cells in these diseases. Accumulating evidence suggests that dysregulation of non-coding RNAs contributes to DC differentiation, functions, and so on, consequently producing effects in various autoimmune diseases. In this review, we summarize the main non-coding RNAs (miRNAs, lncRNAs, circRNAs) that regulate DCs in pathological mechanisms and have tremendous potential to give rise to novel therapeutic targets and strategies for multiple autoimmune diseases and immune tolerance-related diseases.